2015
DOI: 10.1007/s11145-015-9575-y
|View full text |Cite
|
Sign up to set email alerts
|

Language skills and reading comprehension in English monolingual and Spanish–English bilingual children in grades 2–5

Abstract: The present study investigated language skills and reading comprehension with English monolingual and Spanish-English bilingual children in grades 2-5. Of the 377 children in the sample, 207 were English monolingual and 170 were SpanishEnglish bilingual. Data were collected within a cohort-sequential design for two academic years in the fall and spring of each year. Growth modeling was used to estimate initial status on measures of vocabulary breadth, vocabulary depth, morphological awareness, and syntactic sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
31
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 51 publications
10
31
2
Order By: Relevance
“…In the upper elementary and secondary grades, decoding typically becomes more automatic, texts become more linguistically complex, and teachers need to focus more of their instruction on language to keep pace with the comprehension demands of text. This has been shown to be consistent for monolingual and bilingual learners alike (Proctor et al, 2012;Silverman et al, 2015). However, meta-analytic work has shown that bilingual children, relative to monolinguals, are advantaged in thinking about language (i.e., in metalinguistic awareness) because "the experience of acquiring and maintaining two different languages-with different forms and structures-allows bilingual speakers to develop an explicit and articulated understanding of how language works" (Adesope, Lavin, Thompson, & Ungerleider, 2010, p. 209).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In the upper elementary and secondary grades, decoding typically becomes more automatic, texts become more linguistically complex, and teachers need to focus more of their instruction on language to keep pace with the comprehension demands of text. This has been shown to be consistent for monolingual and bilingual learners alike (Proctor et al, 2012;Silverman et al, 2015). However, meta-analytic work has shown that bilingual children, relative to monolinguals, are advantaged in thinking about language (i.e., in metalinguistic awareness) because "the experience of acquiring and maintaining two different languages-with different forms and structures-allows bilingual speakers to develop an explicit and articulated understanding of how language works" (Adesope, Lavin, Thompson, & Ungerleider, 2010, p. 209).…”
Section: Discussionsupporting
confidence: 56%
“…Instruction focused on developing students' understanding about the language components generally but specifically used morphological and syntactic examples from the intervention texts. We chose to focus on morphology and syntax because of their documented relations with both academic language (Brisk & Zhang-Wu, 2017;Uccelli et al, in press) and reading comprehension (Proctor, Silverman, Harring, & Montecillo, 2012;Silverman et al, 2015). In line with previous research, morphology instruction included a focus on common prefixes, suffixes (Baumann et al, 2003;Goodwin & Perkins, 2015;Kieffer & Lesaux, 2007), and root word meanings (Reed, 2008) via word study techniques (Bear, Templeton, & Invernizzi, 2008;Ganske, 1999).…”
Section: Days 3 and 4: Morphology And Syntaxmentioning
confidence: 99%
“…Among various factors loading highly on oral linguistic ability, vocabulary knowledge has been considered as a stronger factor in explaining reading comprehension (Droop & Verhoeven, 2003;Silverman, Proctor, Harring, Hartranft, Doyle & Zelinke, 2015;Verhoeven & van Leeuwe, 2011). This supports Lexical Restructuring Hypothesis (Metsala & Walley, 1998), in that vocabulary knowledge is as a part of oral language, and vocabulary growth has strong effect on the development of reading comprehension.…”
Section: Simple View Of Reading (Svr)supporting
confidence: 64%
“…Previous research has focused on several facets of language proficiency, including vocabulary, morphology, and syntax. Vocabulary knowledge has been consistently found to predict reading comprehension (Liebfreund, ; Silverman et al., ). For example, Droop and Verhoeven () found that reading comprehension in fourth‐grade monolingual and emergent bilingual students was influenced by vocabulary and morphosyntactic knowledge.…”
Section: Previous Researchmentioning
confidence: 99%